Quality Control Strategy On Crab Handling Process By Using Analytical Hierarchy Process Method - Anita Wulandari (Faculty of Agriculture, Merdeka University Surabaya, 2018)
Crab (crab) is one of the fishery products that is generally perishable. This is likely due to poor handling that decreases the quality. This research aims to determine factors that can affect the quality of crab and recommend a priority strategy most appropriate to apply quality control on crab handling at PT Tonga Tiur Putra in expanding its business. The present research uses AHP (Analytical Hierarchy Process) method. Three decision-makers in PT. Tonga Tiur Putra were taken as respondents. Analysis factor reveals that factor affecting the quality of crab meat is transportation. The proper alternative to control the quality of crab is human resource training.